Productivity and profitability of rice (Oryza sativa) varieties grown and nurtured organically on a 5-year old zero chemical applied soil base - AVISHEK PRADHAN; SAR, KOUSHIK; CHOWDHURY, MD RITON; SWAIN, DEEPAK KUMAR; DASH , SUBHAPRADA; GULATI, J M L (The Indian Journal of Agricultural Sciences, 2025)
A field experiment entitled “Productivity and profitability of rice varieties grown and nurtured organically on a 5-year old zero chemical applied soil base” was conducted at Agricultural Research Station, Siksha ‘O’ Anusandhan, Bhubaneswar, Odisha in rainy (Kharif) season 2022. Application of manures was based on recommended dose of nitrogen (RDN) of respective varieties with 50% N (M1) and 100% N (M2) applied half each through FYM and vermicompost. Treatment M3 was devoted to application of organic liquid formulations. Across the treatments, variety Poornbhog was significantly superior with respect to grain yield (3250.1 kg/ha) and associate characters, viz. EBT/m2 (234), number of filled grains (114), panicle length (25.5 cm) and panicle weight (2.8 g) along with highest net return (₹1,33,703/ha) and B-C (2.2). Among the HYV Naveen was significantly superior over Kalinga Dhan 1201. Student's  on a 5-year old zero chemical applied soil base” was conducted at Agricultural Research Station, Siksha ‘O’ Anusandhan, Bhubaneswar, Odisha in rainy (Kharif) season 2022. Application of manures was based on recommended dose of nitrogen (RDN) of respective varieties with 50% N (M1) and 100% N (M2) applied half each through FYM and vermicompost. Treatment M3 was devoted to application of organic liquid formulations. Across the treatments, variety Poornbhog was significantly superior with respect to grain yield (3250.1 kg/ha) and associate characters, viz. EBT/m2 (234), number of filled grains (114), panicle length (25.5 cm) and panicle weight (2.8 g) along with highest net return (₹1,33,703/ha) and B-C (2.2). Among the HYV Naveen was significantly superior over Kalinga Dhan 1201. Student's varieties of both the groups. Treatment M3 produced significantly higher yield (3235.1 kg/ha) along with maximum NR (₹ 94,514/ha) over others. All the varieties under organics showed almost similar plant height, test weight and duration though, Poornabhog and Kalinga Dhan 1201 matured earlier by 10 days than their basic varietal characters. Interaction was significant and all the varieties produced their best under M2 treatments. Application of organic liquid formulations showed favourable effect on yield over M0. Partial factor productivity and recovery efficiency was higher at lower level of N application.